2016
DOI: 10.5380/rabl.v15i1.46144
|View full text |Cite
|
Sign up to set email alerts
|

Optionality in the Use of Too: The Role of Reduction and Similarity

Abstract: Este artigo lida com a propriedade da obrigatoriedade que é frequentemente descrita como uma característica da classe das partículas aditivas (e.g., o advérbio too (“também”)). Em resumo, essas partículas são chamadas de obrigatórias porque omiti-las em um discurso criaria ou um resultado infeliz ou a derivação de inferências indesejadas. Uma linha comum de análise trata essa propriedade como booleana. O consenso geral costuma ser que se uma partícula aditiva pode ser usada num discurso, então ela tem que ser … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 4 publications
0
11
0
1
Order By: Relevance
“…In a corpus study using the London-Lund Corpus of Spoken English (LLC), Spenader (2002) found that too served mainly the purpose of signalling parallel information. Similarly, Amsili et al (2016) found that aussi (French too) signals similarity of the sentence containing aussi -the host sentence -and its antecedent. Varying degrees of similarity between antecedent and host were tested based on the assumption that similarity is marked to a greater extent when the host is reduced via ellipsis or anaphora.…”
Section: Signalling Similaritymentioning
confidence: 91%
See 2 more Smart Citations
“…In a corpus study using the London-Lund Corpus of Spoken English (LLC), Spenader (2002) found that too served mainly the purpose of signalling parallel information. Similarly, Amsili et al (2016) found that aussi (French too) signals similarity of the sentence containing aussi -the host sentence -and its antecedent. Varying degrees of similarity between antecedent and host were tested based on the assumption that similarity is marked to a greater extent when the host is reduced via ellipsis or anaphora.…”
Section: Signalling Similaritymentioning
confidence: 91%
“…For example, in one condition the host sentence was identical to the antecedent (see (8a) for the English equivalent), whereas in the more reduced manipulations the objects were replaced gradually by pronouns (8b-8c). Amsili et al (2016) found that the more reduced the host sentence was -and arguably more similar to the antecedent 3 -the more aussi was preferred by hearers. From the speakers' perspective this would mean that with increasing similarity the pressure to utter additive particles such as too increases.…”
Section: Signalling Similaritymentioning
confidence: 94%
See 1 more Smart Citation
“…There are alternative views on the data maintaining an MP!-based explanation and competition on the presuppositional level. To capture the influence of different discourse factors, Amsili et al (2015), Winterstein (2009) and Winterstein and Zeevat (2012) propose a more complex presupposition of 'too' incorporating a sensitivity to argumentative identity/similarity. The lack of projection illustrated by ( 33) is not straightforward under these accounts.…”
Section: Grammatical Theories Of Implicatures and Mpmentioning
confidence: 99%
“…The claim that additive marking is optional in (33‐b)–(33‐d) is supported by experimental data (Bade, 2016; Bade & Renans, 2021; Bade & Tiemann, 2016). Another empirical observation is that the obligatory insertion of ‘too’ depends on several discourse factors, including enumeration structures (Amsili & Beyssade, 2009), reduction/ellipsis (Amsili et al., 2015), text type (Eckardt & Fränkel, 2012) and clefts/contrast (Bade, 2016; Bade & Renans, 2021). Bade's focus exhaustivity based analysis derives these discourse effects from the relation of focus to exhaustivity more generally.…”
Section: Issues In Current Theories Of Mp!mentioning
confidence: 99%